Internet-based stress management for distressed managers: results from a randomised controlled trial. Issue 2 (30th August 2017) - Persson Asplund, Robert; Dagöö, Jesper; Fjellström, Ida; Niemi, Linnea; Hansson, Katja; Zeraati, Forough; Ziuzina, Masha; Geraedts, Anna; Ljótsson, Brjánn; Carlbring, Per; Andersson, Gerhard
Abstract : Objective: The aim of this randomised controlled trial (RCT) was to evaluate the efficacy of a guided internet-based stress management intervention (iSMI) among distressed managers compared with a attention control group (AC) with full access to treatment-as-usual. Method: A total sample of 117 distressed managers, mainly employed in the healthcare, IT, communication and educational sector, were randomised to either iSMI (n=59) or an AC group (n=58). The iSMI consisted of eight modules including cognitive behavioural stress management and positive management techniques. Participants received a minimal and weekly guidance from a psychologist or master-level psychology student focusing on support, feedback and adherence to the intervention. Self-report data were assessed at pre, post and 6 months after the intervention. The primary outcome was perceived stress (Perceived Stress Scale-14). The secondary outcomes included mental and work-related health outcomes. Results: Participants in the iSMI intervention reported significantly less symptoms of perceived stress (d=0.74, 95% CI 0.30 to 1.19) and burnout (d=0.95, 95% CI 0.53 to 1.37) compared with controls, at postassessment. Significant medium-to-large effect sizes were also found for depression, insomnia and job satisfaction. Long-term effects (6 months) were seen on the mental health outcomes. Conclusion: This is one of the first studies showing that iSMIs can be an effective, accessible and potentially time-effective approach of reducing stress and other mental-related and work-related health symptoms among distressed managers. Future studies are needed addressing distressed managers and the potential of indirect effects on employee stress and satisfaction at work.